2022
DOI: 10.1186/s12903-022-02681-6
|View full text |Cite
|
Sign up to set email alerts
|

The radiological and histological investigation of the dental follicle of asymptomatic impacted mandibular third molars

Abstract: Objectives The indication for removal of asymptomatic fully impacted third molars is still controversial. In this study, radiological and histological investigation of the dental follicle of asymptomatic impacted mandibular third molars was performed, aiming to provide a reference for clinical prophylactic extraction of these teeth. Methods Patients with impacted mandibular third molars were included and the maximum width of the dental follicle aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
4
0
4
Order By: Relevance
“…Se evidenció que la mayor parte de la muestra analizada, es decir, un 84,2% (32) no presentaba infiltrado inflamatorio, restando un total de 15,8% (6) que refleja en el examen histopatológico la presencia de infiltrado inflamatorio en el tejido pericoronario caracterizado (FIGURA 6).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Se evidenció que la mayor parte de la muestra analizada, es decir, un 84,2% (32) no presentaba infiltrado inflamatorio, restando un total de 15,8% (6) que refleja en el examen histopatológico la presencia de infiltrado inflamatorio en el tejido pericoronario caracterizado (FIGURA 6).…”
Section: Resultsunclassified
“…Calderón-Peña JA et al 14 refieren que el QD de tipo inflamatorio constituyo el 60% de los casos examinados, encontrando un infiltrado inflamatorio crónico o mixto; en este sentido sugiere la extracción profiláctica de los terceros molares con el argumento que ellos son generadores de patologías, añadiendo que esta situación persiste como un tema controversial. Li K et al 32 , examinaron folículos dentales normales de terceros molares incluidos, reportaron infiltración inflamatoria con una incidencia del 57,14%; con un aumento del ancho máximo del folículo dental, hubo un aumento en la incidencia y el grado de infiltración de la inflamación crónica inespecífica; señalando que los terceros molares mandibulares impactados asintomáticos tienden a ser extraídos, especialmente en dientes con un ancho máximo de 2-3 mm del folículo dental en el examen radiológico.…”
Section: Resultsunclassified
“…However, few have explored what happened there. Although the dental follicle of asymptomatic impacted mandibular third molars has been investigated from the radiological and histological view [ 25 ], few explored what happened in ERR of M2Ms due to EIM3Ms.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A relationship between the width of the peri-coronal space and the presence of an epithelial lining associated with an impacted tooth has been previously reported. 13,14,15,16 This is not a vast body of literature exploring the domain of inter-rater reliability of dental specialists regarding pathologies and radiolucencies associated with second molars adjacent to an impacted third molar. According to our study, the only radiolucency that rater 1 observed was external resorption.…”
Section: Discussionmentioning
confidence: 99%